2010
DOI: 10.1007/s10763-010-9237-0
|View full text |Cite
|
Sign up to set email alerts
|

Mathematics Homework: A Study of Three Grade Eight Classrooms in Singapore

Abstract: This paper explores the nature and source of mathematics homework and teachers' and students' perspectives about the role of mathematics homework. The subjects of the study are three grade 8 mathematics teachers and 115 of their students. Data from field notes, teacher interviews and student questionnaire are analysed using qualitative methods. The findings show that all 3 teachers gave their students homework for instructional purposes to engage them in consolidating what they were taught in class as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
4
19
0
1
Order By: Relevance
“…| 103 conference feedback) mentioned by the participating teachers are consistent with Cooper's model and extant findings (e.g., Cooper, 2001;Kaur, 2011;Rosário et al, 2015). The current study extends previous research by exploring overlooked aspects related to the purposes of several homework follow-up practices and their associated constraints.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…| 103 conference feedback) mentioned by the participating teachers are consistent with Cooper's model and extant findings (e.g., Cooper, 2001;Kaur, 2011;Rosário et al, 2015). The current study extends previous research by exploring overlooked aspects related to the purposes of several homework follow-up practices and their associated constraints.…”
Section: Discussionsupporting
confidence: 88%
“…To the authors’ knowledge, the current study is the first to explore middle school mathematics teachers’ homework follow‐up practices delivered in class, their purposes for using such practices, and the constraints associated with the delivery of these practices. All homework follow‐up practices (i.e., checking for homework completion, checking homework on the board, and giving individual feedback in the forms of written comments, praise, criticism, and conference feedback) mentioned by the participating teachers are consistent with Cooper’s model and extant findings (e.g., Cooper, ; Kaur, ; Rosário et al, ). The current study extends previous research by exploring overlooked aspects related to the purposes of several homework follow‐up practices and their associated constraints.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…To address these personal and societal needs, the science assessment framework for the TIMSS standards includes two dimensions: a content dimension, specifying the subject matter domains to be assessed within science, and a cognitive dimension, the one used for this study and adapted from Bloom's Taxonomy (Bloom, Engelhardt, Furst, Hill, & Krathwohl, ). It specifies the cognitive domains expected of students as they engage with science content: knowing , applying , reasoning (Kaur, ; NCES, ). Attention to these cognitive dimensions by teachers in science classrooms is essential to the integrated teaching practices described by Shaw and colleagues (), as they enable EL students to engage in complex thinking and collaborative inquiry and to develop scientific understandings and habits of mind.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Both parents and teachers help in children's homework, increase the depth and quality of learning, provides more motivation, responsibility, sense of purpose and confidence, and can contribute to improving student achievement (Hatch, 1998). According to the teachers' point of view, the role of homework is to develop skills and grasp the concepts, to extend the course work to extracurricular time and to develop a sense of responsibility, and according to students point of view homework has functions such as to improve understanding of mathematics concepts, to review and apply the gained knowledge, to develop problem solving skills, to prepare for exams, to understand mistakes, to evaluate learning process and to extend knowledge of mathematics (Kaur, 2011). In 43 of the 50 studies examined for Cooper's (1989) meta-analysis it was found that there is a positive correlation between time spent on homework and success.…”
Section: Introductionmentioning
confidence: 99%